2018
DOI: 10.1097/md.0000000000012223
|View full text |Cite
|
Sign up to set email alerts
|

The use of extracorporeal membrane oxygenation in trauma patients

Abstract: Extracorporeal membrane oxygenation (ECMO) has been increasingly applied for the treatment of patients with trauma. Because a common complication of ECMO is bleeding, the use of ECMO support for patients with trauma was limited in the past. Studies have demonstrated a survival benefit from ECMO support in cases of traumatic lung injury, and it is likely that patients with other types of trauma would also benefit from ECMO support. However, the effect of ECMO in patients with other types of trauma is unknown.Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
1
27
0
1
Order By: Relevance
“…Yet, this is a critical issue in all currently available polytrauma models. Of course, since ECMO therapy is increasingly applied for the treatment of patients with trauma 55 , its in vivo use is indicated for better improvement of the translational interpretation. However, since there are common complications of ECMO limiting its use in patients with trauma 55 , this strategy has to be considered carefully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, this is a critical issue in all currently available polytrauma models. Of course, since ECMO therapy is increasingly applied for the treatment of patients with trauma 55 , its in vivo use is indicated for better improvement of the translational interpretation. However, since there are common complications of ECMO limiting its use in patients with trauma 55 , this strategy has to be considered carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, since ECMO therapy is increasingly applied for the treatment of patients with trauma 55 , its in vivo use is indicated for better improvement of the translational interpretation. However, since there are common complications of ECMO limiting its use in patients with trauma 55 , this strategy has to be considered carefully. Furthermore, ECMO often triggers systemic inflammation, which should be considered if the inflammatory response to polytrauma will be analyzed 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of ECMO in the early phase should be kept in mind and has been described recently in the literature . Although the clinical cases presented here may seem promising, it should be remembered that trauma patients receiving ECMO support and requiring additional surgery during their hospitalization have an increased mortality rate …”
Section: Discussionmentioning
confidence: 83%
“…However, because of the risk of bleeding, the use of vv‐ECMO on multitrauma patients to help perform surgery is still rare and is rarely reported in the literature. A recently published Taiwanese case‐control study reported that trauma patients receiving ECMO support had an increased mortality rate and that they required further surgery during their hospitalization …”
Section: Discussionmentioning
confidence: 99%
“…Some authors [23] (recently proposed the application of heparin-free ECMO, showing good outcomes and no complications. Chen et al [47] used VV ECMO without anticoagulation in 7 polytraumatic patients without any haemorrhagic complications. Other authors proposed the use of half dose of heparin, with the use of heparin-bonded circuits, which allow systemic heparin dose to be decreased by half, from 4 mg/Kg to 1.5 mg/Kg [48].…”
Section: Complications Of Extra Corporeal Therapy Bleeding and Anticmentioning
confidence: 99%